Al-‘Alāqah bayn al-Dīn wa al-Dawlah bi Indūnīsiyā: Tan Malaka wa Ārā’uhu al-Siyāsīyah - Azhar, Khairil (Studia Islamika, 2000)
The present article is about the relation between religion and state as it is discussed by a prominent figure whose contributions to Indonesian politic are out of question. He is Tan Malaka, who has been considered as a radical Marxist activist. Through his works, including Madilog: Materialisme, Dialektika, Logika; Islam dalam Tinjauan Madilog Dari Penjara ke Penjara; Naar De Republiek Indonesie; Tan Malaka shows his deep appreciation to Marxism. That is why, in these works, be pays a great attention to liberation movement and freedom for people both from colonial domination and from feudalism rooted in Indonesian culture.DOI: 10.15408/sdi.v7i2.711